ON RIVER POLLUTION DURING CONSTRUCTION AND CAPITAL REPAIR OF BRIDGES - L. V. Gulitskaya (Nauka i Tehnika, 2012)
The paper describes a problem pertaining to river pollution during construction and capital repair of bridges and some proposals have been given how to solve the problem concerned. The main sources and types of pollution have been determined in the paper. The paper contains recommendations on  decrease of  river pollution during construction, repair and maintenance of bridges